Conflict, migration, and food security: The role of agriculture and rural development - da Silva, José Graziano; Fan, Shenggen (Food and Agriculture Organization of the United Nations, 2017)
The brief presents several policy recommendations to help prevent conflict and to address some of the underlying causes of forced migration: • Build resilience to conflict and other shocks. Early warning systems and social protection programs should be strengthened to help policymakers and populations respond to and mitigate the impact of shocks like rising food prices, losses in agricultural livelihoods, and negative weather events like drought. • Support local agricultural and food economies and markets. This will help rural populations recover after a conflict. Investments in agricultural and rural development play an important role in both preventing and recovering from conflicts. Ensuring that marginalized populations—including women, smallholder farmers, and minority groups—are equitably included in such investments, as well as in the distribution of natural resources, is key in reducing the tensions that often lead to conflict and forced migration. • Let migrant populations work. Neighboring countries that become hosts to refugee populations also have an important role to play in reducing forced migration. Allowing migrants to work both reduces the economic burden on the host country and allows migrants to generate income that they can then bring back to their home countries when and if they return. This can help countries recover more quickly from conflicts.